Intellectual Capital: Its Role in Strengthening the Influence of Accounting Conservatism and Liquidity on Earnings Quality - Ratieh Widhiastuti; Ida Nur Aeni; Wisudani Rahmaningtyas; Novita Della Putri; indah khoirunnisa (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2025)
This study examines the impact of accounting conservatism and liquidity on earnings quality, as well as the moderating effect of intellectual capital. Using panel data from 100 profit-generating infrastructure companies listed from 2020 to 2024, the research employs descriptive statistics and moderated regression analysis. The results show that accounting conservatism significantly improves earnings quality, indicating that conservative reporting provides a stronger credibility signal to stakeholders. Conversely, liquidity has no significant effect on earnings quality. Intellectual capital also fails to moderate the effects of either accounting conservatism or liquidity on earnings quality, suggesting that its organizational placement and measurement may not have a direct influence on financial reporting behavior.  Theoretically, this study contributes to the refinement of signal theory within the context of earnings reporting, demonstrating that only conservatism, rather than liquidity or intellectual capital, functions as a reliable signal of earnings quality. Practically, the findings highlight the need for firms to strengthen conservatism-based reporting policies to enhance stakeholder trust, and they underscore the importance of developing more precise metrics for evaluating intellectual capital in relation to financial reporting outcomes.